Factors Determining Perceived Stress among Medical Students during the Covid-19 Pandemic: fear of COVID-19 and perceived stress in Medical sciences students - Faraji , Amirreza; Ahmadpour , Farhad; Aslani, Armin; Fathnezhad-Kazemi, Azita (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: All viral epidemics are a global health problem and a threat to mental health. Medical sciences students are especially prone to mental health disorders and hence could be more vulnerable to the impact of the COVID-19 pandemic. The aim of the study was to evaluation of perceived stress and its related factors in medical students. Methods: A cross-sectional web-based study was conducted in December 2020 at Islamic Azad University Tabriz Medical sciences. 434 students participated in the study willingly. Socio-demographic characteristics, the level of fear of COVID-19, and perceived stress were collected and analyzed. Results: The results showed that the mean (SD) of fear of COVID-19 and perceived stress were 20.45 (5.52) and 24.70 (7.90), respectively. There was a significant and positive relationship between fear of COVID-19 and perceived stress in students and this effect was moderate (r = 0.465, P < 0.001, medium). According to the findings, fear of COVID-19 solely has the capacity to explain 24.6% of the changes related to perceived stress in students (β = 0.496, SE = 0.003, P < 0.001). Additionally, multivariate regression analysis revealed that fear of COVID-19, employment state, and academic year capable to explain 25.3% of stress changes in students. Conclusions: In this study, there was a positive relationship between fear of COVID-19 disease and perceived stress. It is essential to care and plan in order to reduce the negative influence of COVID-19 on mental health and there is a requirement for proper interventions by specialists in order to maintain mental health, particularly for the medical students who are exposed to the disease.